Pengaruh Kelompok Kerja dan Kompetensi Guru terhadap Mutu Pembelajaran di SD Kecamatan Pampangan OKI - Retno Palupi; Tri Widayatsih; Hery Setiyo Nugroho (Badan Penerbit STIEPARI Press, 2025)
This study aims to determine the effect of teacher work groups and teacher competence on the quality of learning in State Elementary Schools in Pampangan District, OKI Regency. This type of research is quantitative research. The sample in this study was 157 State Elementary School teachers in Pampangan District, OKI Regency. The data collection technique used a questionnaire. The data analysis technique used quantitative descriptive analysis techniques, simple regression and multiple regression tests. The results of this study state that 1) there is an influence of teacher work groups on the quality of learning in State Elementary Schools in Pampangan District, OKI Regency; 2) there is an influence of teacher competence on the quality of learning in State Elementary Schools in Pampangan District, OKI Regency; 3) there is a joint influence of teacher work groups and teacher competence on the quality of learning in Elementary Schools in Pampangan District, OKI Regency.